Design a wireless pressure sensor with an ellipse and a circular shape to monitor the pressure within the coronary artery - Alghrairi, Mokhalad; Sulaiman, Nasri; Wan Hasan, Wan Zuha; Jaafar, Haslina; Mutashar, Saad (IEEE, 2022)
This paper put forward the design and modeling pertaining to a wireless pressure sensor that can monitor blood pressure within the coronary artery with the help of a capacitive pressure sensor. To adjust the resonance frequency (26.78–27.09 MHz) with regards to this sensor’s applied pressure (0–30 KPa), sensor’s dimension as well as human blood pressure (0–220 mmHg), a variable capacitor in the pressure sensor has been put forward. The shape of the capacitive pressure sensor was designed to look like an Ellipse and a circle, which were assessed for their performance with regards to capacitive sensitivity and diaphragm deflection. Also, the diaphragm thickness pertaining to the capacitive pressure sensor with Ellipse and circular shapes was altered ( 0.1 μm to 0.5 μm ) while the cross-section area was kept constant at 1 mm 2 . As per the results, an invasive sensor with circular and Ellipse capacitive pressure shape that had smaller size (1) mm 2 displayed high sensitivity. The sensitivity readings for Ellipse and circular shape capacitive pressure sensor were 7.73 ff mmHg −1 and 9.94 ff mmHg −1 , respectively. Diaphragm deflection was simulated based on the COMSOL Multiphysics software, while MATLAB was employed for simulation with regards to changes in resonance frequency, capacitance, and capacitive sensitivity.